Screening tools as a predictor of injury in gymnastics: Systematic literature review - Armstrong, R.; Relph, N. (Sports Medicine - Open, 2021)
Background Gymnastics requires a high level of physical ability and technical skill which utilises short sets of athleticism and artistry to perform complex and intense movements which can overload musculoskeletal tissues and result in acute injuries which can develop into chronic injuries. The aim of this systematic literature review was to investigate which screening tools predict injury in gymnasts and encompasses all genres, levels and ages.